Erythrocyte Sedimentation Rate and Complete Blood Count Parameters among Female Students of DIII Medical Laboratory Technology, Poltekkes Kemenkes East Kalimantan - Dewi Saraswati; Maria Eka Suryani; Yuliansyah Rianur (PT. Edukasi Ahmad Kirang, 2026)
Background: Erythrocyte Sedimentation Rate (ESR) is a non-specific indicator of systemic inflammation widely used in clinical laboratory practice. Physiological factors including menstrual cycle phase, anemia, and hormonal influences can affect ESR values in women of reproductive age. Female medical laboratory technology students represent an ideal population for studying physiological variation in hematological parameters. This study aimed to describe ESR values and complete blood count (CBC) parameters among female DIII Medical Laboratory Technology students at Poltekkes Kemenkes Kaltim and to analyze their correlation. Methods: This descriptive observational study with a cross-sectional design was conducted at the Hematology Laboratory of Poltekkes Kemenkes Kaltim. A total of 31 female students aged 18–25 years who met the inclusion criteria were enrolled. Blood samples were collected by venipuncture; CBC was examined using a Hematology Analyzer and ESR was measured using the Westergren method. Data were analyzed using descriptive statistics and Spearman correlation (α=0.05). Informed consent was obtained from all participants. Results: The mean ESR was 20.74 ± 16.38 mm/h (median 18.00 mm/h, IQR 11.5–28.5, range 1–76 mm/h); Shapiro-Wilk test confirmed non-normal distribution (W=0.8937; p=0.005). Based on the Westergren reference value for adult women (≤20 mm/h), 58.1% of subjects had normal ESR and 41.9% had elevated ESR. Mean hemoglobin was 13.01 g/dL with 12.9% classified as mildly anemic. Mean leukocyte count was 8,143 cells/µL with a normal differential. Spearman correlation analysis revealed no statistically significant correlation between ESR and all CBC parameters (p>0.05), although a borderline correlation was found between ESR and lymphocytes (rho=0.343; p=0.059). Conclusion: ESR values in apparently healthy female students showed wide variability, with 41.9% exceeding the normal reference limit, reflecting the influence of physiological factors—particularly menstrual cycle phase and hormonal status—rather than pathological processes. No significant correlation was found between ESR and CBC parameters, likely due to the narrow hemoglobin range in the study population. These findings emphasize the importance of considering physiological context when interpreting ESR in women of reproductive age. Longitudinal studies recording menstrual cycle phases are recommended.